The relationship between some endometrial secretion cytokines and in vitro fertilization - Mohammad Ehsan Rahiminejad; Amirhossein Moaddab; Mehrnoosh Ebrahimi; Soghra Rabiee; Alireza Zamani; Mohammad Ezzati; Alireza Abdollah Shamshirsaz (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Endometrial secretion analysis is a non-invasive and promising method in evaluation of endometrial receptivity. Objective: The aim of the present study was to assess the relationship between the success rate of IVF procedures and some endometrial secretion cytokines, including interleukin-1β (IL-1β), tumor necrosis factor (TNF-α), interferon gamma-induced protein 10 (IP-10), and monocyte chemoattractant protein (MCP). Materials and Methods: In a prospective cohort study, 50 women selected for IVF met the study inclusion criteria. All the patients underwent endometrial secretion aspiration prior to embryo transfer. The level of IL-1β, TNF-α, IP-10 and MCP were analyzed by enzyme-linked immunosorbent assay method using special standard kits. To detect successful implantation and pregnancy patients underwent serum human chorionic gonadotropin measurements and ultrasound evaluation. Results: Five samples were excluded. Nine women (20%) had successful clinical pregnancies, which resulted in live birth. Other 36 women (80%) were classified as failed pregnancy. Comparison of cytokine levels showed lower concentrations of TNF-α, IP-10, and MCP in the group with successful clinical pregnancy compared to the group with failed pregnancy (p=0.007, 0.005 and 0.001, respectively). However, no significant difference was revealed in IL-1β levels between two groups (p=0.614). Conclusion: The current study suggested that lower concentrations of TNF-α, IP-10, and MCP in endometrial secretions might be associated with improved endometrial receptivity and IVF outcome. Regarding IL-1β, no statistically significant differences were seen between the groups with and without successful pregnancy.